Genetic etiology of DNA-mismatch repair deficiency in cancer - Rosa, Reginaldo Cruz Alves (2022)
DNA mismatch repair (MMR) is a highly conserved pathway that maintains genomic integrity by repairing base-base mismatches and insertion-deletion loops generated during DNA replication. MMR deficiency is detected in a substantial fraction of tumors, especially endometrial cancer (EC), and is used as an indicator of cancer predisposition and a marker of resistance to certain chemotherapies, such as 6-thioguanine (6-TG). Germline and somatic inactivation of MLH1, MSH2, MSH6, and PMS2 genes, which encode the main components of the MMR pathway, is the leading cause of MMR deficiency. However, some MMR-deficient tumors do not harbor any alteration in MMR genes, suggesting that other genes could also drive the MMR-deficient (MMR-D) phenotype in cancer. To investigate the genetic etiologies of MMR deficiency, we established a Brazilian cohort of 242 EC cases and assessed the MMR status on tumors by immunohistochemistry, microsatellite instability, and MLH1-methylation. MMR deficiency was detected in 38.4% of tumors, and germline mutation in the main MMR genes was investigated in 37 MMR-D cases. We found germline pathogenic variants in 10/37 (27%) patients. Next, we explored the etiology of the 27 unexplained MMR-D tumors by germline and somatic next-generation sequencing of 63 genes related to cancer-predisposition and DNA repair. Germline variants in ATM, ATR, CHEK2, FAN1 and MUTYH genes were found in 26% of cases and were associated with a pronounced family history of cancer. Tumor sequencing revealed inactivating mutations in MMR genes, mainly in MSH6, as the leading cause of MMR deficiency in EC. Mutations in the exonuclease domain of POLE were found to be a frequent driver of MMR deficiency, probably by increasing mutation rates, resulting in the inactivation of MMR genes. Previous studies have identified WDHD1, an essential component of the eukaryotic replisome, as an MSH2 partner. Therefore, we constructed a Wdhd1-mutant cell line by CRISPR/Cas9 and interrogated the impact of the disrupted WDHD1-MSH2 interaction on the repair of replication errors and sensitivity to 6-TG. Disruption of WDHD1- MSH2 interaction did not increase the number of spontaneous mutations and did not lead to an MSI phenotype. On the other hand, Wdhd1-mutant cells acquired mild resistance to 6-TG. In conclusion, we have confirmed the inactivation of MMR genes as the main cause of MMR deficiency in EC. Additionally, germline mutations in other DNA repair genes are found in individuals with MMR-D tumors and may explain the high cancer incidence in their relatives. Finally, WDHD1 is not an alternative driver of MMR deficiency but might participate in the MMR-mediated response to 6-TG.